Quantitative Evaluation of Visitation Dynamics and Audience Segmentation for Sustainable Management of Civil War Memorial Heritage in Alicante, Spain - Rosser Limiñana, Pablo; Soler, Seila (BP International, 2024)
This study assesses the impact of visits to the Civil War shelters in Alicante as key elements of memorial cultural heritage, using a quantitative approach and data collected between August 2023 and January 2024 Through visitor segmentation, diverse visitor profiles were identified. Time series analysis observed patterns of visits without a clear trend, although ARIMA models predicted a slight stabilization of demand. The segmentation revealed two distinct groups of visitors, highlighting the importance of adapting dissemination and heritage education strategies. The findings underscore the significance of the shelters as tools for conservation and heritage education, suggesting the need for personalized approaches to enhance the visitor experience and promote the preservation of cultural heritage. This analysis provides valuable evidence for effective heritage management and tourism planning.
Keywords: cultural heritage; sustainable tourism; time series analysis; visitor segmentation; ARIMA models